The genetics of resistance to cocoyam root rot blight complex disease in Xanthosoma sagittifolium(L.)Schott - Agueguia, A.; Fatokun, C.; Hahn, S.K. (International Society for Horticultural Science, 1994)
Six hybrid cocoyam clones from a uniform yield trial and a Local White accession from the germplasm collection were crossed in a diallel excluding reciprocals, in order to determine the inheritance pattern of resistance to cocoyam root rot blight complex (CRRBC) disease. The 21 progenies from this diallel crossing program were evaluated for CRRBC disease resistance in a randomized complete block design in 4 replications. The progenies showed varying levels of resistance to CRRBC disease. The diallel cross analysis revealed that variation for CRRBC resistance in cocoyam is mainly as a result of additive gene effects. The predominance of general combining ability over specific combining ability in the inheritance of resistance to CRRBC is an indication that efforts need not be wasted in the search for identification of heterotic combinations.